Company Performance and Corporate Social Responsibility - Zarkasi Zarkasi; Sufyati HS; Darmawati Manda; Deddy Novie Citra Arta (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
This study seeks empirical evidence on the impact of independent variables, namely corporate social responsibility and state, as moderating variables on firm performance. The purposive sampling technique was used to analyze a sample of 7 companies in the construction sub-sector listed on the Indonesia Stock Exchange between 2019 and 2022. Panel data regression and descriptive statistics were employed in this study. The study's findings show that corporate social responsibility has a positive but non-significant effect on firm performance, and that the state does not moderate the effect of corporate social responsibility on firm performance.